Factors associated with birth weight in Sweden: the study of men born in 1913. Issue 1 (February 1997) - Eriksson, M; Cnattingius, S; Svärdsudd, K; Tibblin, G
Abstract : STUDY OBJECTIVE: To analyse factors associated with birth weight and to evaluate the validity of obstetrical data. DESIGN: Obstetrical data were retrieved for singleton men born in 1913 and living in Gothenburg, Sweden in 1963. Information on birth weight, maternal age, marital status, parity, social class, proteinuria, gestational age, and place of birth (home or hospital) was obtained from these birth records. SETTING: Sweden. PARTICIPANTS: Fifty year old men living in Gothenburg, Sweden, in 1963. MAIN RESULTS: Obstetrical records were obtained for 524 men (65%). Place of birth, gestational age, maternal age, parity, proteinuria, and marital status were all significantly correlated to birth weight. In multivariate analyses, place of birth, gestational age, parity, and proteinuria influenced birth weight. There was a substantial difference in mean birth weight between hospital deliveries (3352 g) and home deliveries (3817 g), which could be explained only partly by sociodemographic variables. Birth weight increased with parity and gestational age in home delivered babies as well as those delivered in a hospital. CONCLUSIONS: The validity of obstetrical records from 1913 was good. The place of birth (home or hospital) is strongly associated with birth weight and may be a confounding factor in studies of the implications of birth weight for future risk of disease or death.